Phase-sensitive radar (ApRES) time series data from Thwaites eastern ice shelf, 2020 ... - Nicholls, Keith; Holland, David (NERC EDS UK Polar Data Centre, 2022)
The dataset comprises ApRES (Autonomous phase-sensitive Radio Echo Sounder) time series from four sites (G1-4) through the grounding zone of the eastern Thwaites ice shelf. The instruments were deployed in early 2020 and recovered in early 2021 as part of the International Thwaites Glacier Collaboration (ITGC) MELT project. The aim was to provide time series of basal melt rates and the vertical strain rate at each site. The ApRES DAT files were converted to netCDF for publication. Each burst in an ApRES file maps straightforwardly to a group in the corresponding netCDF file. This is a lossless, reversible process. The data were acquired under funding from ITGC: NE/S006656/1. ... : The datasets were collected using standard ApRES methodology with instrument configuration described in data headers. The radar bandwidth was 200 MHz, centred on 300 MHz with a 1-second chirp length at a power of 20 dBm. Bursts of 20 chirps were collected at 2-hourly intervals. The ApRES DAT files were converted to netCDF for publication, using the bas-apres Python package. ...